Glasshouse acclimatization of tissue-cultured Melastoma malabathricum plantlets - Abdullah, Janna Ong; Rohidin, R.; Mahmood, Maziah (2006)
Tissue-cultured Melastoma malabathricum plants were acclimatized to glasshouse conditions by leaving them for 7 or 14 days in open jars in distilled water or washed and kept in a covered aquarium. Plants in the aquarium had a higher survival rate than those open jars and grew to greater heights.